Role of Fluid and Sodium Retention in Experimental Ventilator-Induced Lung Injury - Gattarello, Simone; Pasticci, Iacopo; Busana, Mattia; Lazzari, Stefano; Palermo, Paola; Palumbo, Maria Michela; Romitti, Federica; Steinberg, Irene; Collino, Francesca; Vassalli, Francesco; Langer, Thomas; Moerer, Onnen; et al. (Frontiers in Physiology, 2021)
Background: Ventilator-induced lung injury (VILI) via respiratory mechanics is deeply interwoven with hemodynamic, kidney and fluid/electrolyte changes. We aimed to assess the role of positive fluid balance in the framework of ventilation-induced lung injury. Methods:Post-hoc analysis of seventy-eight pigs invasively ventilated for 48 h with mechanical power ranging from 18 to 137 J/min and divided into two groups: high vs. low pleural pressure (10.0 ± 2.8 vs. 4.4 ± 1.5 cmH2O; p < 0.01). Respiratory mechanics, hemodynamics, fluid, sodium and osmotic balances, were assessed at 0, 6, 12, 24, 48 h. Sodium distribution between intracellular, extracellular and non-osmotic sodium storage compartments was estimated assuming osmotic equilibrium. Lung weight, wet-to-dry ratios of lung, kidney, liver, bowel and muscle were measured at the end of the experiment. Results: High pleural pressure group had significant higher cardiac output (2.96 ± 0.92 vs. 3.41 ± 1.68 L/min; p < 0.01), use of norepinephrine/epinephrine (1.76 ± 3.31 vs. 5.79 ± 9.69 mcg/kg; p < 0.01) and total fluid infusions (3.06 ± 2.32 vs. 4.04 ± 3.04 L; p < 0.01). This hemodynamic status was associated with significantly increased sodium and fluid retention (at 48 h, respectively, 601.3 ± 334.7 vs. 1073.2 ± 525.9 mmol, p < 0.01; and 2.99 ± 2.54 vs. 6.66 ± 3.87 L, p < 0.01). Ten percent of the infused sodium was stored in an osmotically inactive compartment. Increasing fluid and sodium retention was positively associated with lung-weight (R2 = 0.43, p < 0.01; R2 = 0.48, p < 0.01) and with wet-to-dry ratio of the lungs (R2 = 0.14, p < 0.01; R2 = 0.18, p < 0.01) and kidneys (R2 = 0.11, p = 0.02; R2 = 0.12, p = 0.01). Conclusion: Increased mechanical power and pleural pressures dictated an increase in hemodynamic support resulting in proportionally increased sodium and fluid retention and pulmonary edema.